2021
DOI: 10.1371/journal.pone.0250569
|View full text |Cite
|
Sign up to set email alerts
|

Profiles and outcomes in patients with COVID-19 admitted to wards of a French oncohematological hospital: A clustering approach

Abstract: Objectives Although some prognostic factors for COVID-19 were consistently identified across the studies, differences were found for other factors that could be due to the characteristics of the study populations and the variables incorporated into the statistical model. We aimed to a priori identify specific patient profiles and then assess their association with the outcomes in COVID-19 patients with respiratory symptoms admitted specifically to hospital wards. Methods We conducted a retrospective single-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
4
4
0
Order By: Relevance
“…Nevertheless, this cluster had the second highest number of patients with renal disease and cancer, surpassed only by cluster 4. This is similar to what was found in a French study, in which only 4% of patients in cluster 1 had acute renal failure (Bondeelle et al, 2021;Cholankeril et al, 2020;Pan et al, 2020;Tian et al, 2020;Zhang et al, 2020).…”
Section: Cluster Analysis Based On Clarasupporting
confidence: 91%
See 4 more Smart Citations
“…Nevertheless, this cluster had the second highest number of patients with renal disease and cancer, surpassed only by cluster 4. This is similar to what was found in a French study, in which only 4% of patients in cluster 1 had acute renal failure (Bondeelle et al, 2021;Cholankeril et al, 2020;Pan et al, 2020;Tian et al, 2020;Zhang et al, 2020).…”
Section: Cluster Analysis Based On Clarasupporting
confidence: 91%
“…Cluster 2 presented a high frequency of patients with risk factors for COVID-19 including cardiovascular disease, diabetes, obesity, and pulmonary disease, and was only surpassed by the "severe" cluster 3. These results partially coincide with a cluster study conducted in France, which showed a higher proportion of systemic, respiratory, and gastrointestinal symptoms in cluster 3, characterized by the highest survival rate in oncohematology patients (Bondeelle et al, 2021). Our findings also partially coincide with those of study performed in China, in which cough was predominant in group B, classified as "intermediate-severe."…”
Section: Cluster Analysis Based On Clarasupporting
confidence: 89%
See 3 more Smart Citations